On Jordan (σ,τ) - Higher Reverse Derivations on Rings - Dr. Fawaz Raad Jarullah, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In this study we introduced the concepts of (,)-higher reverse derivation and Jordan (,)-higher reverse derivation of rings where , be endomorphism. The definition of Jordan triple (,)-higher reverse derivation was deduced. The most important findings of this paper are as follows that : every Jordan (,)-higher reverse derivation is a (,)-higher reverse derivation of R . The results have confirmed that every Jordan (,)-higher reverse derivation is a (,)-higher reverse derivation within certain conditions.
Keywords: (,)-higher reverse derivation; Jordan (,)-higher reverse derivation